Economic evaluation in clinical trials - Glick, Henry A.; Doshi, Jalpa A.; Sonnad, Seema S. (Handbooks in health economic evaluation series., 2014)
It is increasingly important to examine the relationship between the outcomes of a clinical trial and the costs of the medical therapy under study. This book provides a practical guide to the techniques and issues involved in conducting economic evaluation in ongoing clinical trials, supported with examples.